A-properness and fixed point theorems for dissipative type maps - K. Q. Lan; J. R. L. Webb (Abstract and Applied Analysis)
We obtain new A-properness results for demicontinuous, dissipative type mappings defined only on closed convex subsets of a Banach space X with uniformly convex dual and which satisfy a property called weakly inward. The method relies on a new property of the duality mapping in such spaces. New fixed point results are obtained by utilising a theory of fixed point index.